Analysis of notifications of pediatric accidents in São Paulo, SP, Brazil - Rodrigues, Cintia Leci; Armond, Jane de Eston; Iamarino, Ana Paula Marconi; dos Santos, Ana Carolina Giolo; Armond, Rodrigo de Eston; Górios, Carlos (Journal of Health Care, 2017)
Objective: To analyze data of accidents with children recorded in the service network of the Unified Health System (SUS) and in the Surveillance System for Violence and Accident (VIVA) of São Paulo (SP) in the period of January to December 2015. Methods: This is a cross-sectional study, with quantitative, descriptive and retrospective approach. The study covered the totality of 16,847 children aged 0 to 9 years, victims of accidents, reported in VIVA of the Municipal Health Secretariat of São Paulo, in which accidents and violence reports are recorded by the suspected or confirmed case notification form. Results: In children of all ages of the surveyed group and in both genders, accidental falls were the most recorded type of accident: they occurred in children aged between 0 and 4 years (63.9%); 5 to 9 years (36.1%). Regarding gender, 39.1% of the accidents occurred in females and 60.9% among male children. Conclusion: This study showed that the main type of accident were accidental falls occurred predominantly at home and with males. It was noted in this study that we are facing vulnerable children who need special care, mainly preventive, in intersectoral action with health and education agencies and professionals that are involved in monitoring the growth and development of children.